Establecimiento de una red de valoración de pureza atmosférica en la provincia de La Coruña (España) mediante bioindicadores liquénicos - Crespo, Ana; Barreno, Eva; Sancho, Leopoldo G.; Bueno, Antonio G. (Lazaroa, 1981)
Crespo, A., Barreno, E., Sancho, L. O. & Bueno, A. G. Atmospherical purity valoration net established in La Coruña province (Spain) using lichenio bioindicators. Lazaroa, 3: 289-311 (1981). The epiphytic lichen Flora around the coal power síation of Meirama (La Coruña, Spain) is studied. Three biocenolic indexes are síablished IAP, diversity (D) and fre is proposed. A catalogue of the species quency (F) and a qualitative toxisensibility scale of epiphytic lichens that have been recognized is also presented including 70 new records fo, dic arce.